The role of sharing creative ideas: professional designers about their work - Rojek-Adamek, Paulina (Creativity Studies, 2021)
A characteristic feature of the transition from industrial to post-industrial society is basing a significant part of production on the “intangible” value (software production, audiovisual production, advertising, design, cultural activities, etc.). The individual is perceived as the main actor in management processes where professional success depends on readiness for dialogue and exchange of owned capital (not only economically). It means a different definition of work, perceiving it as an element of shaping – understood in many dimensions – social, economic and cultural relations. Dematerialization of work means therefore giving primacy to the handling of information. This phenomenon can also be seen as a manifestation of cognitive capitalism characterized as a different accumulation system which is based on knowledge and creativity, in other words, on forms of intangible investment. Therefore, it seems that it would be particularly valuable to examine the potential of groups that have this knowledge capital as the basis of their activity. The article will discuss the theoretical concept of the exchange and sharing of creative ideas in the design field. It also presents original research devoted to this issue, conducted in the environment of Polish designers.